Patients with asthma have reduced functional capacity and sedentary behavior - Mariana Mazzuca Reimberg; Jessyca Rodrigues Selman Pachi; Rebeca Souza Scalco; Andrey Jorge Serra; Leandro Fernandes; Fabiano Politti; Gustavo Falbo Wandalsen; Dirceu Solé; Simone Dal Corso; Fernanda Cordoba Lanza (Elsevier, 2020)
Objective: The modified shuttle test is a field test that avoids the ceiling effect, and there are no reports of a multidimensional assessment concerning physical activity in asthmatic patients. Thus, the aim was to evaluate functional capacity by MST, additionally to perform a multidimensional assessment as physical activity in daily life, muscle strength, and cytokine levels in children and adolescents with asthma, and to correlate these variables. Method: This cross-sectional study included volunteers aged between 6 and 18 years who were divided into two groups: asthma group (n = 43) that received regular treatment and control group (n = 24). Functional capacity was evaluated by distance walked during the MST; physical activity in daily life was evaluated using an accelerometer by the number of steps. Quadriceps femoris strength was evaluated by load cell. Results: Distance walked was lower for the asthma group (790 m [222 m]) when compared with the control group (950 m [240 m]; p = 0.007); however, the number of steps was similar between the two groups (asthma group: 7743 [3075]; control group: 7181 [3040]; p = 0.41), and both groups were classified as sedentary behavior. There was no difference in muscle strength. Tumor necrosis factor-α differed, but interleukin levels were similar between groups. Quadriceps strength was correlated to distance walked (r = 0.62; p < 0.001) and tumor necrosis factor-α to the number of steps taken (r = −0.54, p = 0.005). Conclusion: Children and adolescents undergoing regular asthma treatment showed reduced functional capacity and sedentary behavior. The lower the quadriceps strength, the shorter the distance walked; the higher the tumor necrosis factor-α levels, the lower their daily physical activity levels. Resumo: Objetivo: O Teste Shuttle Modificado é um teste clínico de campo que evita o efeito-teto e não existem relatos de avaliação multidimensional com relação à atividade física em pacientes com asma. Assim, o objetivo era avaliar a capacidade funcional pelo shuttle teste, adicionalmente, realizar avaliação multidimensional através da a atividade física na vida cotidiana, a força muscular e os níveis de citocina em crianças e adolescentes com asma, a fim de correlacionar essas variáveis. Método: Este estudo transversal incluiu voluntários entre seis a 18 anos, os quais foram divididos em dois grupos: o grupo com asma (n = 43), que recebeu tratamento regular, e o grupo de controle (n = 24). A capacidade funcional foi avaliada pela distância percorrida durante o Teste Shuttle Modificado, ao passo que a atividade física na vida cotidiana foi avaliada utilizando um acelerômetro pelo número de passos. A força muscular do quadríceps femoral foi avaliada por uma célula de carga. Resultados: A distância percorrida foi menor no grupo com asma (790 m [222 m]) em comparação com o grupo de controle (950 m [240 m]; p = 0,007), contudo o número de passos foi semelhante nos dois grupos (grupo com asma: 7.743 [3.075]; grupo de controle: 7.181 [3.040]; p = 0,41) e ambos os grupos foram classificados como sedentários. Não houve diferença na avaliação da força muscular. O fator de necrose tumoral-α apresentou divergências, porém os níveis de interleucina foram semelhantes entre os grupos. A força muscular do quadríceps foi correlacionada com a distância percorrida (r: 0,62; p < 0,001) e o fator de necrose tumoral-α, ao número de passos dados (r = −0,54, p = 0,005). Conclusão: Crianças e adolescentes que recebem tratamento regular de asma apresentaram redução da capacidade funcional e comportamento sedentário. Quanto menor a força muscular do quadríceps, menor a distância percorrida; quanto maiores os níveis de fator de necrose tumoral-α, menores seus níveis diários de atividade física. Keywords: Asthma, Functional capacity, Number of steps, Muscle strength, Inflammatory profile, Palavras-chave: Asma, Capacidade funcional, Número de passos, Força muscular, Perfil inflamatório